Board of Directors, Ownership Structure, Regulation and Bank Performance: What Can Change After the Financial Crisis - Zgarni, Amina (International Journal of Economics and Financial Issues, 2018)
This study focuses on comparing the impact of governance on the performance of banks before and after the subprime crisis. The review of the empirical literature on this theme earlier helped to highlight that bank governance is characterized by the importance of external mechanisms (such as regulation) as well as internal (mainly the board of directors and ownership structure) and that the adoption of these mechanisms does not always affect the performance of banks. However, several failure of governance in banking may be behind the outbreak of crisis. Thus we were interested in comparing the contribution of governance mechanisms to performance before and after the subprime crisis. Empirical validation from a sample of Tunisian commercial banks quoted, observed over two different periods (1990–2006) and (2007–2010) shows that governance, in the period before the crisis, significantly influences both the operating and stock market performance and net banking income of these institutions and, this in different ways, through the regulatory solvency ratio, the size of the board of directors, its composition, its dual structure, and through the ownership structure. Similarly, the size, age and the number of bank branches show different a significant effect on the performance of banks. However, the crisis appears to weaken the effectiveness of governance in view of bank performance. Indeed, after the crisis, governance appears to have a negative effect on accounting performance (only through the liquidity ratio), a positive effect on stock market performance (only through the duality and the solvency ratio) and it is no effect on net banking income. Keywords: Governance, Board of Directors, Ownership Structure, Subprime Crisis, Bank Performance, Regulation JEL Classifications: G3, G32